Potential för värmeåtervinning från mjölkkylanläggningar - Karlsson, Emelie (SLU/Dept. of Energy and Technology, 2012)
The present climate discussion has made energy efficiency an interesting topic. Saving energy does not only help the climate but also saves money for the energy consumer.